Killing two birds with one stone: emergence of colistin and cefiderocol resistance in a mucoid MDR Acinetobacter baumannii under colistin pressure - Fox, Valeria; Vrenna, Gianluca; Rossitto, Martina; Paris, Irene; Papa, Rosanna; Artini, Marco; Selan, Laura; Raimondi, Serena; Tuccio Guarna Assanti, Vanessa; Essa, Nour; Lepanto, Maria Stefania; Cortazzo, Venere; et al. (Frontiers in Microbiology, 2025)
Acinetobacter baumannii is a multidrug-resistant (MDR) pathogen associated with nosocomial infections, sporadically detected in cystic fibrosis (CF) patients. Treatment of A. baumannii may be hindered by polysaccharide capsule production of some isolates and extended resistance to most antibiotics. In these fearsome cases, colistin (COL) and cefiderocol (FDC) are considered last resort antibiotics. Unfortunately, resistance to these molecules is increasing. Indeed, we observed a hypermucoid (HM) A. baumannii strain producing OXA-23, isolated from a CF patient, rapidly evolving concomitant resistance to COL and FDC. At her first visit to our hospital, the 24-year-old female with a delayed CF diagnosis and advanced lung disease presented with one HM and one low mucoid (LM) A. baumannii phenotypes. Due to Pseudomonas aeruginosa infection, she received inhaled tobramycin and COL treatment. Five months later, two HM strains were isolated, with different susceptibility profiles to COL and FDC, one being completely resistant. Whole genome sequencing revealed that all four isolates, the initial HM and LM strains and the two subsequent HM strains, belonged to Sequence Type 2 and carried OXA-23 gene. Genetic distance revealed evolution from the same strain. HM strains carried mutations in genes involved in polysaccharide production while the resistant strain also harboured mutations conferring COL and FDC resistance. Biofilm production and motility of the four strains were evaluated to establish possible links between multiresistance, mucoidity and virulence. Phenotypic characterisation showed that HM strains lost some virulence traits during chronicisation and resistance development but likely persisted by exploiting the biofilm-mediated protection, maintaining both virulent and resistant subpopulations. We speculate that COL treatment forced A. baumannii resistance occurrence in a bacterial population already heteroresistant to FDC, resulting in a pan-resistant strain in this CF patient. Considering that lung transplantation still represents a life-saving option for CF patient with advanced lung disease, this study highlights the critical need for careful administration of last-resort molecules in patients that may face immunosuppression. Indeed, given the possibility of simultaneous emergence of resistance and the limited treatment options available to patients infected with MDR A. baumannii, last-resort antibiotics should be spared to avoid selection of pan-resistant microorganisms.